'I just Love Research': Beliefs about What Makes Researchers Successful. (4th July 2018) - Wylie, Caitlin Donahue
Abstract: There is a longstanding belief that research should be a calling more than a job. How does this expectation shape the selection of future researchers? Specifically, undergraduate research experience is credited with increasing students' success in science and engineering majors and their likelihood to choose careers in science and engineering; thus, how researchers select student laboratory workers has implications for the future population of researchers. After all, because research communities construct knowledge collectively, researchers' identities and experiences crucially shape knowledge. This paper analyzes qualitative interviews with engineering professors and students about what they believe are the characteristics of a good researcher. Both groups describe the importance of a researcher feeling interested in and enthusiastic about research to be able to do good work. They also imply that good researchers must be assertive, such as by requesting jobs in laboratories. I suggest that these explicit and implicit expectations can create opportunities for implicit bias and unintentional exclusion and suggest strategies to mitigate these problems and promote inclusion for the next generation of researchers.